Impacts of SARS-CoV-2 on brain renin angiotensin system related signaling and its subsequent complications on brain: A theoretical perspective - Etebar, Negar; Naderpour, Saghi; Akbari, Setareh; Zali, Alireza; Akhlaghdoust, Meisam; Daghighi, Seyed Mojtaba; Rahimzadegan, Milad (Elsevier, 2024)
Cellular ACE2 (cACE2), a vital component of the renin-angiotensin system (RAS), possesses catalytic activity to maintain AngII and Ang 1-7 balance, which is necessary to prevent harmful effects of AngII/AT2R and promote protective pathways of Ang (1- 7)/MasR and Ang (1-7)/AT2R. Hemostasis of the brain-RAS is essential for maintaining normal central nervous system (CNS) function. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a viral disease that causes multi-organ dysfunction. SARS-CoV-2 mainly uses cACE2 to enter the cells and cause its downregulation. This, in turn, prevents the conversion of Ang II to Ang (1-7) and disrupts the normal balance of brain-RAS. Brain-RAS disturbances give rise to one of the pathological pathways in which SARS-CoV-2 suppresses neuroprotective pathways and induces inflammatory cytokines and reactive oxygen species. Finally, these impairments lead to neuroinflammation, neuronal injury, and neurological complications. In conclusion, the influence of RAS on various processes within the brain has significant implications for the neurological manifestations associated with COVID-19. These effects include sensory disturbances, such as ol- factory and gustatory dysfunctions, as well as cerebrovascular and brain stem-related disorders, all of which are intertwined with disruptions in the RAS homeostasis of the brain.
Keywords: COVID-19; Angiotensin signaling; MasR signaling; Renin-angiotensin system; Neuroinflammation